Childhood atopic eczema: children’s Quality of life and family impact - Ghani, Ahmad Abir Ab (2012)
Childhood atopic eczema accounted 40% of the referral to pediatric dermatology clinic in Malaysia. One of the most important issues that should be discussed during outpatient hospital based clinic is health related quality of life (HRQOL). HRQOL was defined as a broad multidimensional concept that usually includes self-reported measures of physical and mental health. The current study was aimed to determine the quality of life of children with atopic eczema, impact of atopic eczema to the family and associated factors for children’s quality-of-life. A cross-sectional study conducted at Dermatology clinic, Hospital Raja Perempuan Zainab II, Kota Bharu, Malaysia from January 2010 to January 2011. Children who were diagnosed as atopic eczema, aged between 5 and 18 years and fulfilled the inclusion and exclusion criteria were selected using systematic random sampling. Qualityof- life (Qol) was measured using CDLQI. Family Impact was measured using DFI. The Children’s Dermatology Life Quality Index (CDLQI) and Dermatology Family Impact (DFI) questionnaires were specifically designed to measure Qol of children with atopic eczema and the family impact of the similar disease. Data were analyzed according to distributions. Descriptive analyses were done for quality of life and family impact score and univariate and multivariate analyses were done to determine associated factors for Qol. Results: A total of 110 participants with 100% response rate entered this study. Majority of subjects suffered mild to moderate disease which comprised of 30.9% and 62.7%, respectively. Only 6.4% had severe atopic eczema. The median (IQR) for quality of life and family impact score was 8.0 (8.0) and 7.0 (9.0), respectively. Disease severity was the significant associated factor for quality of life in childhood atopic eczema. Regression analyses showed that 15% of the variance in quality of life score could be explained by disease severity score. In the present study, the overall children’s quality of life was not impaired because not all the items in the children’s quality of life were equally affected. Childhood atopic eczema also had no impact on family life as majority of parents perceived the disease was not severe. The only significant associated factor for children’s quality of life was disease severity. Measurement of HRQOL among childhood atopic eczema should be done along with objective disease severity assessment.